The Governance of Subsidized LPG: Global Perspective from Systematic Review - Rochman, Naufal Noor; Rahayu, Amy Yayuk Sri; Atmoko, Andreo Wahyudi (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2024)
This study aims to investigate the governance of subsidized liquid petroleum gas (LPG) distribution on a global scale by conducting a systematic review of the existing literature. It is meant to find the major determinants of effective LPG subsidy programs and bring out difficulties and prospects that face equitable accessibility to clean cooking fuel. The researchers carried out a systematic literature review, according to the PRISMA guidelines, to collect and assess empirical studies regarding LPG subsidy programs. It consist of 58 publications that were released from 2009 to 2024 and were chosen for their importance in collaborative governance. Starting conditions and institutional design were found to be essential for the success of LPG subsidy programs. The conclusion is that power imbalances and trust problems among stakeholders must be addressed to foster the collaboration effectiveness. Leadership also plays a key role in navigating the complex stakeholder dynamics and ensuring the sustainability of these programs. This study provide a better understanding of the factors that improve or hinder the effectiveness of LPG subsidy programs. This study also provides valuable guidance to policymakers and stakeholders involved in energy subsidies by synthesizing global findings.